2014
DOI: 10.3389/fpsyg.2014.00365
|View full text |Cite
|
Sign up to set email alerts
|

Processing word prosody—behavioral and neuroimaging evidence for heterogeneous performance in a language with variable stress

Abstract: In the present behavioral and fMRI study, we investigated for the first time interindividual variability in word stress processing in a language with variable stress position (German) in order to identify behavioral predictors and neural correlates underlying these differences. It has been argued that speakers of languages with variable stress should perform relatively well in tasks tapping into the representation and processing of word stress, given that this is a relevant feature of their language. Neverthel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 78 publications
4
13
0
Order By: Relevance
“…Different psychoacoustic measures have been used to assess ATP abilities. Among them are gap detection [e.g., 2,3], duration discrimination [e.g., 4,5], spectral temporal order judgment (TOJ) [e.g., 1,2,6,7], and dichotic TOJ [e.g., 1,2,6,7]. These tasks have been studied among healthy young participants and in comparison to different populations, such as aphasic patients [8][9][10][11], dyslexic readers [12][13][14][15][16], aging adults [1,6,7,[17][18][19], children with autistic spectrum disorders [20], children and young adults with attention deficit/hyperactivity disorder [21,22], and sleep-deprived young adults [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Different psychoacoustic measures have been used to assess ATP abilities. Among them are gap detection [e.g., 2,3], duration discrimination [e.g., 4,5], spectral temporal order judgment (TOJ) [e.g., 1,2,6,7], and dichotic TOJ [e.g., 1,2,6,7]. These tasks have been studied among healthy young participants and in comparison to different populations, such as aphasic patients [8][9][10][11], dyslexic readers [12][13][14][15][16], aging adults [1,6,7,[17][18][19], children with autistic spectrum disorders [20], children and young adults with attention deficit/hyperactivity disorder [21,22], and sleep-deprived young adults [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, previous research has shown that stress processing depends crucially upon memory load (e.g., Dupoux et al, 1997, 2001; Peperkamp et al, 2010; Domahs F. et al, 2014; Heisterueber et al, 2014). For example, Dupoux et al (1997) found that in an ABX task French participants had significantly more difficulties in lexical stress discrimination than Spanish participants, while in an AX task French participants could accurately detect the acoustic correlates of lexical stress.…”
Section: Introductionmentioning
confidence: 99%
“…These results demonstrated the role of short-term memory in stress abilities. Heisterueber et al (2014) also reported that at both the behavioral and neuro-functional levels German speakers exhibited inter-individual differences in word stress processing, which might be attributed to individual working memory (WM) span. Moreover, in a non-word reading task Domahs F. et al (2014) found that German speakers’ individual WM capacity was positively correlated with their assignment of main stress to the antepenultimate syllable, and negatively correlated with the assignment of stress to the final syllable.…”
Section: Introductionmentioning
confidence: 99%
“…We wanted to use the fact that there is a large degree of interindividual heterogeneity in word stress assignment, at least partly related to WM ( Heisterueber et al, 2014 ). Specifically, it was predicted that the proportion of computationally complex APU stress assignment across stimuli should be positively correlated with the individual WM capacity.…”
Section: Introductionmentioning
confidence: 99%